2016
DOI: 10.1038/nature20587
|View full text |Cite|
|
Sign up to set email alerts
|

Gamma frequency entrainment attenuates amyloid load and modifies microglia

Abstract: Changes in gamma oscillations (20-50 Hz) have been observed in several neurological disorders. However, the relationship between gamma and cellular pathologies is unclear. Here, we show reduced behaviorally-driven gamma before the onset of plaque formation or cognitive decline in a mouse model of Alzheimer's disease (AD). Optogenetically driving FS-PV-interneurons at gamma (40 Hz), but not other frequencies, reduced levels of amyloid-β (A β)1-40 and A β1-42 isoforms. Gene expression profiling revealed inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
1,110
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 963 publications
(1,163 citation statements)
references
References 42 publications
46
1,110
4
3
Order By: Relevance
“…This approach could also be implemented within transgenic animals (Reijmers et al, 2007) to further expand the number of cell types targeted. The results of our experiment stimulating excitatory neurons at 40 Hz are consistent with previous reports that periodic stimulation with blue laser light can activate and entrain ChR2-expressing neurons (Boyden et al, 2005) and LFP power at those frequencies (Iaccarino et al, 2016). Interestingly, we also found that periodic silencing of the inhibitory neurons could also entrain cortical rhythms, likely through disinhibition of the excitatory neurons and/or post-illumination rebound of inhibitory neurons (Chuong et al, 2014) or both.…”
Section: Discussionsupporting
confidence: 92%
“…This approach could also be implemented within transgenic animals (Reijmers et al, 2007) to further expand the number of cell types targeted. The results of our experiment stimulating excitatory neurons at 40 Hz are consistent with previous reports that periodic stimulation with blue laser light can activate and entrain ChR2-expressing neurons (Boyden et al, 2005) and LFP power at those frequencies (Iaccarino et al, 2016). Interestingly, we also found that periodic silencing of the inhibitory neurons could also entrain cortical rhythms, likely through disinhibition of the excitatory neurons and/or post-illumination rebound of inhibitory neurons (Chuong et al, 2014) or both.…”
Section: Discussionsupporting
confidence: 92%
“…RNA sequencing analysis showed an increase in phagocytic genes, such as Cd68, β 2 -microglobulin (B2m), Icam, and lysozyme 2 (Lyz2), and in the proliferation markers Csf1, Csf1r, and Csf2ra. Notably, levels of proinflammatory genes (Il1b, Il6, Cd11b) and antiinflammatory genes (Igf1) were not changed (158), suggesting that it is possible to use immunomodulation to polarize microglia toward a beneficial activation state that is characterized…”
Section: Optogenics In Activation Of Microgliamentioning
confidence: 99%
“…Gamma oscillations arise from the activation of local circuits of excitatory and fast-spiking inhibitory neurons resonating at 20-50 Hz, and changes in gamma oscillation have been observed in neurological diseases (158). Interestingly, entraining gamma oscillation at 40 Hz in 5xFAD mice induced amyloid reductions that were associated with an increase in microglial numbers and morphological changes such as soma enlargement and shortening of processes loaded with Aβ.…”
Section: Optogenics In Activation Of Microgliamentioning
confidence: 99%
“…2). Interesting, a recent study by Iaccarino et al demonstrated that entraining gamma oscillations (20 to 40 Hz), which is different from LLLT, may provide systemic effects in the brain to attenuate AD-related pathology through modulation of microglia [48]. Further study in gamma oscillations and LLLT is warranted to examine whether it will have therapeutic effects in human AD.…”
Section: Lllt Regulates/modulates Multiple Intracellular Down-stream mentioning
confidence: 99%